Penanaman Nilai Akhlak Santri Pondok Pesantren Mu’allimin Muhammadiyah Pakan Sinayan - Tri Wulan Dari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this research is: (1) To describe and know how moral values are instilled in the students of Mu'allimin Muhammadiyah Feed Sinayan Boarding School (2) To know the supporting and hindering factors that support and hinder the behavior of Mu'allimin Boarding School Muhammadiyah students Allimin Muhammad Feed Sinayan Boarding School. The study was a field study using qualitative methods. Mu'allimin Muhammadiyah Boarding School Leadership and Ustadzah Research Topic, Sinayan Feed and Research Object: Mu'allimin Muhammadiyah Moral Value Development as well as Factors Supporting and Hindering the Moral Value Development. The data collection methods used included interviews, observation and documentation. The data collection method was conducted through data reduction, data presentation and conclusion drawing. The results of this study show that the development of moral values among the students of Mu’allimin Muhammadiyah Boarding House occurs through the study of the Qur’an, prophets, role models and habits inside and outside the classroom. method. The Quran, the Prophet, Examples and Customary Ways. Moral values instilled in the boarding school Mualimin Muhammadiyah feed among others: Moral values are taught in the classroom playground before learning begins, students greet the teacher every change of class, when the teacher comes, students sit when ustadzan accustomed to sit down to eat and drink, and if you meet the ustadzah you have to be polite in speaking and doing something. Supporting factors and inhibiting factors are equally environmental factors.